GEOCHEMISTRY OF SODIC WATERS IN THE DATONG INTERMOUNTAIN BASIN, SHANXI PROVINCE, NORTHWESTERN CHINA - Shvartsev S.L.; Wang Y. (My University, 2006)
The paper presents a critical analysis of current concepts of the origin of sodic waters. The example of the Datong Basin with widespread sodic waters is employed to demonstrate that these waters typically have salinities of 0.6-4.5 g/l at pH of 7.8-8.8. It was determined that sodic waters are in equilibrium with calcite and clay minerals (montmorillonite and kaolinite) and, sometimes, also with analcime but are never in equilibrium with anorthite, albite, forsterite, microcline, and muscovite; i.e., the water-rock system is in equilibrium-unequilibrium state. The degree of evaporation concentration of salts is in places as high as a few tens. The complex analyses of conditions under which sodic waters are formed indicates that these waters are produced during a certain weathering stage of aluminosilicates, after the groundwaters have reached equilibrium with calcite. The time when this equilibrium can be reached is controlled by the intensity of the water exchange. © Pleiades Publishing, Inc. 2006.